PERKEMBANGAN PENERAPAN PRINSIP KONSERVATISME DALAM AKUNTANSI - Riri Zelmiyanti (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2014)
This paper tried to see the development of the application of the principle of conservatism in accounting. In the previous study researchers directly see how the implementation of the application of the principle ofconservatism. Whereas in this study tried to see the beginning of conservatism in accounting principles to theInternational Financial Report Standards (IFRS) or more towards the development of the principle ofconservatism. This study also gives some examples of the implementation of the accounting standards. Theexistence of the financial statements of the international harmonization of accounting, affecting theimplementation of the principle of conservatism in the company. The desire IFRS produce financial statementsthat could predict future circumstances contrary to the principle of conservatism, so the application of theprinciple of conservatism began to be reduced. But because of the level of uncertainty within the company led tothe principle of conservatism can not be eliminated completely, so that the current IFRS issued a new principle,namely prudence.